(untitled) (Journal of the Bangladesh Agricultural University, 2010)
The paper reports the first incidence of successful induction of breeding in the riverine catfish Rita rita using carp pituitary gland (PG) extract. A breeding trial using four PG doses viz. 80, 100, 120 and 140mg/kg body weight of fish was conducted to optimize the dose of pituitary gland (PG) extract in terms of induction of ovulation in female. The male received a dose of 40mg PG/kg body weight in all cases and was sacrificed for collection of milt. The best performance was shown by the fish treated with 100mg PG/kg body weight in respect of inducing ovulation in females and fertilization and hatching rates of eggs. Keywords: Induced breeding; Rita rita; Ovulation; Fertilization rate; Hatching rate DOI: 10.3329/jbau.v6i2.4835 J. Bangladesh Agril. Univ. 6(2): 361-366, 2008